Isolation, characterisation and development of genetic tools for methane-oxidising bacteria - Rumah, Bashir Lawal (2019)
Methane is an important greenhouse gas (GHG) and a source of energy for heating, lighting, generation of electricity and growth of methanotrophs. In addition to balancing CH4 levels in the environment, methanotrophs can be used to produce platform chemicals like lactate; biopolymers such as poly-3-hydroxybutyrate (PHB) and animal feed in the form of single cell proteins. To harness their industrial and environmental potential, this study was carried out to understand their physiology, biochemistry and to develop the much needed forward and reverse genetic tools in methane fixing bacteria. Nine methanotrophs were isolated using dilution to extinction methods and streaking on dilute Nitrate Mineral Salt (dNMS) agar plates. They include Isolate 01 (Methylocystis species) isolated from Wollaton late; Isolate 03 (Methylocystis species) also isolated from Wollaton lake; Isolate 3* (Methylocystis species) isolated from a bog in Moseley; Isolate 6 (Methylocystis species) isolated from University Of Nottingham lake, Isolate 7 (Methylomonas species) isolated from Nottingham landfill; Isolate 9 (Methylococcus capsulatus) isolated from a landfill in Nigeria; Isolate 10 (Methylocaldum species) isolated from cow manure; Isolate 12 (Methylocystis species) also isolated from a bog in Moseley; and Isolate 14 (Methylococcus capsulatus) isolate from Roman baths in Bath. Isolate 6 and Isolate 10 are type I; Isolate 9 and 14 are type X; while Isolate 01, 03, 3*, 6 and 12 are type II methanotrophs. All the isolates were able to grow both on CH4 and biogas. Only the type II methanotrophs were capable of accumulating PHB under nitrogen limiting conditions with Isolate 12 accumulating approximately 10 times more PHB (25.05% of dry cell weight) when grown with biogas compared to CH4. The important characteristics, availability of PacBio genome sequence and good conjugation efficiency of Isolate 12 qualified it as the best candidate for the development of transposon random mutagenesis in methanotrophs. A Tn5 plasmid derivative (miniTn5Kan_R6K) was used to deliver the transposon, and Inverse PCR identified 36 different insertion locations of transposon suggesting unbiased transposition insertions. A suicide plasmid replicon (R6K) was used for the plasmid and its non-replicative nature was demonstrated in Isolate 12. It was the first time random transposon mutagenesis was reported in type II methanotrophs. To enable more efficient genome editing, CRISPR-Cas9 gene knockout system was attempted on four methanotrophs (Isolate 3*, 10, 12 and M. parvus OBBP). Gene knockout was achieved in Isolate 12 and M. parvus (OBBP) when DNA ligase IV gene (ligD) was targeted using a plasmid with guide RNA under the transcriptional control of a promoter with moderate strength and Streptococcus pyogenes Cas9 under the transcriptional control of a weak promoter. Up to 80% editing efficiency was achieved in Isolate 12. This is the first demonstration of CRISPR genome editing in methanotrophs.